2006
DOI: 10.1007/s10549-006-9317-6
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor genomic heterogeneity in breast cancer with clonal divergence between primary carcinomas and lymph node metastases

Abstract: Conflicting theories of epithelial carcinogenesis disagree on the clonal composition of primary tumors and on the time at which metastases occur. In order to study the spatial distribution of disparate clonal populations within breast carcinomas and the extent of the genetic relationship between primary tumors and regional metastases, we have analyzed by comparative genomic hybridization 122 tissue samples from altogether 60 breast cancer patients, including 34 tumor samples obtained from different quadrants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
103
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(120 citation statements)
references
References 30 publications
14
103
0
3
Order By: Relevance
“…In agreement with our results, previous studies using conventional comparative genomic hybridization or loss-of-heterozygosity techniques have described the existence of intra-tumour heterogeneity in a significant proportion of breast cancers [47][48][49], and the analyses of matched ductal carcinoma in situ and invasive carcinoma [49,50] or matched invasive . Unsupervised hierarchical cluster analysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our results, previous studies using conventional comparative genomic hybridization or loss-of-heterozygosity techniques have described the existence of intra-tumour heterogeneity in a significant proportion of breast cancers [47][48][49], and the analyses of matched ductal carcinoma in situ and invasive carcinoma [49,50] or matched invasive . Unsupervised hierarchical cluster analysis.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, some studies have suggested that metastases may occur early during carcinogenesis and follow a distinct clonal progression [46,47]. This is unlikely, however, as the breakpoints of 17q12 amplification in the primary tumour components and metastatic deposit were identical.…”
Section: Fc Geyer Et Almentioning
confidence: 99%
“…However, this finding likely reflects the heterogeneity of different clones of cells having different genetic profiles that are present within a primary tumor, which is related to the multistage process of cancer development. Our results and others from primary breast tumors suggest frequent intratumoral heterogeneity of genetic aberrations 12,15,[35][36][37][38] implying a coexistence, within the same mass of primary tumor, of different cell subpopulations with different genetic profiles. Metastasis is likely established by a minority of cells from the primary tumor, which migrate to a single distant site.…”
Section: Discussionsupporting
confidence: 70%
“…[7][8][9][10] Primary tumors and matched ALN metastases from breast cancer patients have been studied by low-resolution genomic approaches for assessment of copy number changes, such as metaphase CGH, allelic imbalance and low-resolution array-CGH. [11][12][13][14] In one report using metaphase CGH, 12 divergence between the primary tumors and ALN metastases was noted in several cases. In another recent report, genome-wide array-CGH with average resolution of 1 Mb per data point was used in the analysis of ALN metastases and primary tumors from 29 patients.…”
Section: Introductionmentioning
confidence: 99%
“…65 Also, multiple research groups have shown that individual breast tumors contain significant mutational heterogeneity. 66 For example, using FISH, Aubele and colleagues 67 found that different cells from the same invasive breast tumor had different chromosomal gains and losses. Likewise, Torres and others 66 showed that primary breast carcinomas are composed of several genetically heterogeneous and spatially separated cell populations using CGH, and Fujii and coworkers 64 identified distinct allelic losses in different cells from the same in situ breast cancer.…”
Section: The Cancer Stem Cell Hypothesismentioning
confidence: 99%